Ultralow thermal conductivity and low charge carrier scattering potential in Zn1-xCdxSb solid solutions for thermoelectric application. (June 2019) - Biswas, R.; Mukherjee, S.; Mallik, R.C.; Vitta, S.; Dasgupta, T.
Abstract: Zinc Antimonide (ZnSb) is a promising p-type thermoelectric (TE) material for mid-temperature (room temperature to 673 K) power generation application due to its high TE conversion efficiency and low cost. Here we show that further improvements of the TE efficiency of ZnSb is possible by reduction of the lattice thermal conductivity ( κ L ) . This is achieved by forming a solid solution between ZnSb and CdSb which enhance the phonon scattering due to the mass disorder/strain effect. Compositions of Zn1-x Cdx Sb (x = 0, 0.25, 0.375 and 0.5) have been synthesized by melting, rapid compaction followed by annealing. The formation of the solid solution is confirmed from X-ray Diffraction (XRD) measurements and the calculated lattice parameters indicate an expected increase with Cd content. Thermoelectric properties have been measured between room temperature and 673 K. It is observed that the lattice thermal conductivity ( κ L ) is significantly reduced by this alloying. At room temperature ∼ 50% reduction is achieved for x = 0.5 composition, while at elevated temperatures (523 K) a κ L value 0.62 W m −1 K −1 is obtained for x = 0.375 composition. The reduction in κ L is attributed to the additional contribution to the phonon scattering by mass/strain disorder based on fitting the room temperature κ L data with the Klemens-Callaway model. A significant contribution to the lowering of κ L in the solid solutions is found to be due to the anharmonic nature of the bonding. The effect of alloying on the electrical properties have been further investigated and results indicate low alloy scattering ( U ) potential ∼0.3 eV in the solid solutions. The possible origin of such low U values is further an indicator of the muti-center, anharmonic nature of bonding in this system. Thus, the ultra-low lattice thermal conductivity coupled with low alloy scattering potential make Zn1-x Cdx Sb ideal candidates for further enhancement in thermoelectric efficiency. Graphical abstract: Image 1